Advanced computational techniques for solving partial differential equations in fluid dynamics and spectral domains - Abbas, Basim K. (Edelweiss Applied Science and Technology, 2025)
The article provides an algorithmic exploration of the motion of fluids, including the solution to Poisson's equation across specified areas employing spectral approaches. The Poisson problem has been solved on an annular field, resulting in a nearly-zero uniform resolution over the area, suggesting great numerical accuracy. Velocity and pressure patterns have been established within a rectangular realm, and the findings corresponded throughout the vertical as well as horizontal elements, having near-zero values indicating an evenly simulated system. Furthermore, both velocity scalar sectors and maxima contour graphs exhibited consistent flow characteristics and variable velocity magnitudes, which are important for comprehending fluid dynamics in restricted situations. The present investigation presents an innovative use of spectral approaches for handling complicated, unusual field geometries like circular and rectangular domains, which are generally difficult to account for using typical finite element computation or infinite difference approaches. The method merely boosts the effectiveness of computation; however, it additionally enhances solution precision in boundary-sensitive systems such as fluid mechanics. The newly developed incorporation of this approach within the inquiry of fluid behavior under shifting boundary conditions opens the door to more rigorous calculations in commercial and academic software, representing a substantial advance in the computational investigation of equations involving partial differentials.